Broken bridges: an exchange of slurs between African Americans and second generation Nigerians and the impact on identity formation among the second generation. (November 2015) - Imoagene, Onoso
Abstract: This article examines the use of slurs between members of different ethnic groups within the black racial category in the United States—specifically, the second generation of Nigerian ancestry and African Americans, as reported by the second generation of Nigerian ancestry. Studies on inter-group usage of slurs have mostly focused on the use of racial slurs targeting African Americans, the use of racial and ethnic slurs targeting non-black racial/ethnic groups, and the use of sexist slurs targeting people of different gender and sexual orientation. There has been limited analysis of use of slurs between ethnic groups within the black racial category in the United States. My investigation shows that slurs are part of the process of identity formation for the second generation. Also, the use of slurs between these two ethnic groups within the black category provides more evidence for Croom's (2010, 2011, and 2013) point that slurs do not always have to be used in a derogatory manner. It adds to what we know about the nonderogatory use of slurs by showing that a slur can be used as a socialization tool for young in-group members. I show that slurs can be appropriated by the group using the slur to target out-group members and that slurs can also be used within their own group to send a cautionary message to group members based on the derogatory meanings that are infused into the slur. Highlights: The article investigates inter-ethnic relations between black ethnic groups. This article examines the use of slurs among black ethnics in the United States. It examines the role of slurs in identity formation. Uses the family resemblance model to analyze the slurs African booty scratcher and Akata. Offers a new two-way process of how slurs are appropriated.